Through the Spectacles of a Non-believer: Diasporic Images of the Antilles, Africa and Latin America in V.S. Naipaul’s "A Way in the World" - Javangwe, Tasiyana D. (2016)
This article seeks to interrogate the fractured identity images of the Antilles, Africa and Latin America in V.S. Naipaul's collection of memoirs and essays in A Way in the World (1994). It argues that Naipaul's reading and interpretation of the cultural and identity crisis in these regions suffers from a self inflicted alienation that has made him unable to appreciate the possibility of a new beginning at the end of slavery, indentureship and colonialism. Naipaul in this regard becomes a typical non-believer whose vision of the Caribbeans, Africa and Latin America is blighted by images of cyclic futility, macabre circumstances of existence, violence and primordial ritualism.